ANALISIS BIBLIOMETRIK: TREN PUBLIKASI PENELITIAN PERPUSTAKAAN ISLAM DI INDONESIA - Wahyudin, Rama (UIN Imam Bonjol Padang, 2023)
The intensity of research developments related to Islamic Libraries has grown from 1985 to 2023 in Indonesia. Various contributions of researchers have succeeded in revealing innovations in the field of libraries, especially in the scope of Islamic religiosity. However, along with its development, research that is always being developed only focuses on a few objects, including research that focuses on Islamic institutions and on general matters such as benefits, services, and the like. This study aims to reveal research trends that have developed from 1985 to 2023 to obtain results in the form of an overview and visualization of research results related to Islamic Libraries. The method used is Quantitative with Bibliometric analysis. The results show that, the researcher obtained 970 items as Meta Data obtained from the Publish Or Perish application, then extracted using Microsoft Excel and analyzing the Vosvewers Application, the picture obtained, Islamic literature needs special attention especially on Gap and Novelty, considering that there are so many studies which only focuses on benefits, services, qualitative methods, links with the world of education such as Madrasas, Islamic Boarding Schools, High Schools to Islamic Universities such as UIN, IAIN, and STAI. The research concept that becomes an innovation for Islamic libraries that needs to be developed is research related to Bibliometric Analysis such as Risk Management, Contribution to Digitalization, Economics, Business, Information, to those related to management such as HR, Institutions, certain structures, collaborations, and library techniques that innovative.